ANALISIS FUNGSI JOSHI “MO” DALAM MANGA YAKUSOKU NO NEVERLAND KARYA KAIU SHIRAI - Cici Yulistri; Hendri Zalman (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2021)
This study aims to determine the function of joshi "mo" in Manga Yakusoku No Neverland by Kaiu Shirai. This type of research is qualitative research using descriptive methods.  The data used in this study were sentences containing joshi "mo" in Manga Yakusoku No Neverland by Kaiu Shirai. The data sources were taken from the Manga Yakusoku No Neverland by Kaiu Shirai volume 13-18 which consists of 55 chapters.  Based on the results of the study, it was found that there were 6 functions of joshi "mo" belonging to the fukujoshi group, namely showing the same thing as the others;  means “also”, the form “... mo... mo... も...も...” indicates several things that are all the same “both .... and ....;  and .... also ", is used in a renegade form to indicate" .... not even .... ", following the interrogative pronoun to indicate the meaning of all not, following the number one, indicating absolutely not, following degrees or a large or many number  ;  "to".  In addition, there is also found 1 joshi function "mo" which is included in setsuzokujoshi, namely the form "-te / de mo ～ て / で も" which shows the meaning of "even though;  although;  even though ”.